Mutation Update and Review of Severe Methylenetetrahydrofolate Reductase Deficiency. Issue 5 (18th March 2016) - Froese, D. Sean; Huemer, Martina; Suormala, Terttu; Burda, Patricie; Coelho, David; Guéant, Jean‐Louis; Landolt, Markus A.; Kožich, Viktor; Fowler, Brian; Baumgartner, Matthias R.
Abstract : This mutation update collates all known patients (192, in 171 families) and mutations (109) associated with severe MTHFR deficiency. The majority of mutations are of the missense type, predominantly found in the N‐terminal catalytic domain. In severe MTHFR deficiency, lower enzymatic activity correlates with early onset (<1 year) disease, suggesting residual enzymatic function is an important determinant of disease. ABSTRACT: Severe 5, 10‐methylenetetrahydrofolate reductase (MTHFR) deficiency is caused by mutations in the MTHFR gene and results in hyperhomocysteinemia and varying severity of disease, ranging from neonatal lethal to adult onset. Including those described here, 109 MTHFR mutations have been reported in 171 families, consisting of 70 missense mutations, 17 that primarily affect splicing, 11 nonsense mutations, seven small deletions, two no‐stop mutations, one small duplication, and one large duplication. Only 36% of mutations recur in unrelated families, indicating that most are "private." The most common mutation is c.1530A>G (numbered from NM_005957.4, p.Lys510 = ) causing a splicing defect, found in 13 families; the most common missense mutation is c.1129C>T (p.Arg377Cys) identified in 10 families. To increase disease understanding, we report enzymatic activity, detected mutations, and clinical onset information (early, <1 year; or late, >1 year) for all published patients available, demonstrating that patients with early onset have less residual enzyme activity than those presenting later. We also review animal models, diagnostic approaches, clinical presentations, and treatment options. This is the first large review of mutations in MTHFR, highlighting the wide spectrum of disease‐causing mutations.